Disentangling Digital Influences on Tourist Behavior: The Role of Trust and Destination Image in the Social Media Era - Sutrisno, Rivan; Rafdinal, Wahyu; Septyandi, Chandra Budi; Gaffar, Mohammad Rizal; Susanto, Eko (Integrasi Sains Media, 2024)
The rise of social media has reshaped how tourists perceive, evaluate, and decide upon travel destinations. This study investigates the direct effects of influencer credibility, content quality, visual aesthetics, and social engagement on tourist trust, destination image, and visit intention. Drawing upon a cross-sectional survey of 232 Indonesian social media users, the proposed structural model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that influencer credibility and visual aesthetics are key drivers of tourist trust, while content quality and visual aesthetics significantly shape destination image. Tourist trust also plays a central role by directly influencing both destination image and visit intention. These findings offer theoretical insight into the psychological mechanisms underlying digital persuasion in tourism and provide actionable strategies for destination marketers and content creators to enhance engagement and conversion through credible and aesthetically compelling influencer content.